The Holy Spirit at work today - Walvoord, John F. (Lincoln, Neb., Back to the Bible Broadcast, 1973)
Lloyd M. Perry Collection.
Reprint of the Moody Press edition.
"Chapters 1-5 are reprinted, with changes, from the series of articles, 'Contemporary issues in the doctrine of the Holy Spirit,' Bibliotheca sacra, 130-31 (1973-74)."
Keywords: Holy Spirit; Gifts, Spiritual